Effect of ganglioside combined with pramexol in the treatment of Parkinson’s disease and its effect on motor function: Ganglioside combined with pramexol for Parkinson’s disease - Li, Xinna; Han, Peihai; Liu, Mengjiao; Li, Xiaowen; Xue, Shuai (Journal of Medical Biochemistry, 2023)
Background: This study was aimed to evaluate the efficacy of pramipexole combined with ganglioside for PD treatment and pramipexole monotherapy, so as to provide reference for clinical practice. Methods: 61 PD patients selected from June 2019 to December 2020 at our hospital were divided into two groups. The control group (n=31) was given dopasizide oral treatment, and the treatment group (n=30) was given ganglioside combined with pramipexole. The clinical efficacy, adverse reactions, motor function scores, UPDRS scores, PDQ-39 scale scores, TNF-α levels, and related serum factor levels were measured. Results: Compared with control group, the total effective rate was obviously increased. The CRP and TNF–α levels, the speech tone and speed, sitting and walking posture, writing and hands ability scores were reduced, while the BDNF level was increased in treatment group. During the period, compared with the control group, the incidence of adverse reactions in the treatment group was significantly decreased. Conclusions: Ganglioside combined with pramipexole was effective in treating PD. It can effectively reduce the level of CRP and TNF-α, increase the level of BDNF, improve neurological function, improve motor function, and does not increase the adverse reactions of patients. It is worthy of application.